2007
DOI: 10.1213/01.ane.0000253668.10453.de
|View full text |Cite
|
Sign up to set email alerts
|

Does Ondansetron or Granisetron Prevent Subarachnoid Morphine-Induced Pruritus After Cesarean Delivery?

Abstract: Neither prophylactic ondansetron nor granisetron reduced the incidence of subarachnoid morphine-induced pruritus when compared with the saline group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 16 publications
3
43
0
Order By: Relevance
“…Pruritus is the most frequent side effect of intrathecal morphine and the incidence in this study (87%) was consistent with previous research. 24 As expected, pruritus was less common and severe in the oral oxycodone group, possibly because of lower opioid concentrations in relevant central nervous areas following systemic administration.…”
Section: Discussionsupporting
confidence: 59%
“…Pruritus is the most frequent side effect of intrathecal morphine and the incidence in this study (87%) was consistent with previous research. 24 As expected, pruritus was less common and severe in the oral oxycodone group, possibly because of lower opioid concentrations in relevant central nervous areas following systemic administration.…”
Section: Discussionsupporting
confidence: 59%
“…Unfortunately the incidence of pruritus in the obstetric population, especially after subarachnoid opioids, can be very high ranging between 70 and 93%. [4][5][6][7]9 This is consistent with our population among whom the incidence of pruritus in ondansetron and granisetron groups was 92.5% and 95% respectively. One of the possible mechanisms of pruritus is related to direct stimulation of 5-HT3 receptors by morphine in the dorsal horn of the spinal cord and medulla, therefore 5-HT3 antagonists may be beneficial in its treatment.…”
Section: Discussionsupporting
confidence: 90%
“…However, the overall incidence of pruritus has not been shown to be reduced with granisetron in patients undergoing caesarean section who received subarachnoid morphine. 9 Although the overall incidence of pruritus is not decreased, what is not clear is whether the prophylactic administration of a long acting 5-HT3 antagonist like granisetron reduces the severity of pruritus, thus improving maternal satisfaction. To our knowledge, no studies have been powered to detect a reduction in severity of pruritus with a long acting 5-HT3 antagonist.…”
Section: Introductionmentioning
confidence: 99%
“…2a. Twenty-one studies were excluded from the analysis because they reported zero events in all arms [39, 43, 57, 60, 61, 71, 73, 81, 82, 86, 90, 9294, 98, 110, 121, 127, 145, 155, 156]. Although the definitions of arrhythmia varied across the studies (Additional file 1: Appendix 10), there was no evidence of network inconsistency ( χ 2 = 3.49, degrees of freedom = 10, P = 0.968, heterogeneity variance = 0.01), and the within-network heterogeneity variance was estimated to be 0.00.…”
Section: Resultsmentioning
confidence: 99%